IDENTIFYING FAULT ACTIVITY IN THE CENTRAL EVOIKOS GULF (GREECE) - Rondoyanni, Th.; Galanakis, D.; Georgiou, Ch.; Baskoutas, I. (Bulletin of the Geological Society of Greece, 2007)
Geological mapping on a 1:5.000 scale and a tectonic analysis in the wider Chalkida region of the Island of Evia and the adjacent Drossia area of Central Greece, have allowed the identification of a number of active and potentially active normal faults. These faults have been formed or reactivated during the Late Quaternary, since they affect Pleistocene brackish and terrestrial deposits. Some of the faults affect the contact of the limestone bedrock with the Quaternary formations, presenting characteristic polished surfaces. The faults, in places covered by the alluvial deposits of the Chalkida plain, are also detected by geophysical research. Among the identified faults, the most important are considered the Aghios Minas- Chalkida, the Avlida and the Lefkadi active faults. The first one extends from Drossia to the Chalkida area, crossing the sea straights, and has an ENE-WSW direction and a south dip. The other two, are parallel antithetic faults oriented WNW-ESE, and bound the South Evoikos Gulf on the Greek mainland and the Evia Island respectively. The mapping and evaluation of active faults in this region of moderate seismicity, with low topographic relief and consequent absence of morphotectonic features, is especially important from a seismic hazard point of view.